Anti‐sulfatide/galactocerebroside antibodies in immunoglobulin M paraproteinemic neuropathies. (7th August 2017) - Boso, F.; Ruggero, S.; Giannotta, C.; Benedetti, L.; Marfia, G. A.; Ermani, M.; Campagnolo, M.; Salvalaggio, A.; Gallia, F.; De Michelis, C.; Visentin, A.; Bianco, M.; et al.
Abstract : Background and purpose: Anti‐sulfatide antibodies have been observed in heterogeneous neuropathies and their clinical relevance is still controversial. Whether the combination of sulfatide with galactocerebroside would increase sensitivity or specificity of enzyme‐linked immunosorbent assay testing compared to sulfatide alone was assessed. Methods: Immunoglobulin M (IgM) antibodies to sulfatides, galactocerebroside and combined sulfatide and galactocerebroside (Sulf/GalC) were measured in 229 neuropathy patients, including 73 with IgM paraproteinemic neuropathy [62 with anti‐myelin‐associated glycoprotein (anti‐MAG) antibody] and 156 with other neuropathies. Results from 27 patients with IgM monoclonal gammopathy without neuropathy and 28 healthy subjects served as control. Results: Thirty‐three patients showed increased titers of anti‐sulfatide antibodies, 28 of whom had an IgM paraproteinemic neuropathy ( P < 0.0001). When evaluating the reactivity for the combination Sulf/GalC, 57/229 patients were found to be positive, including 36/73 (49%) with IgM paraproteinemic neuropathy ( P < 0.0001). Patients with known anti‐sulfatide antibodies also showed anti‐Sulf/GalC reactivity, with increased titers in 48.5% of the cases. Testing for anti‐Sulf/GalC antibodies allowed 24 additional patients to be detected (eight with IgM paraproteinemic neuropathies), who had no reactivity to the individual glycolipids. Amongst the 11 subjects with IgM paraproteinemic neuropathy who were negative for anti‐MAG antibodies, only two were reactive to sulfatide, whilst six (55%) were found to be positive when tested against the combination of sulfatide and galactocerebroside. Conclusions: Testing for both sulfatide and galactocerebroside in IgM paraproteinemic neuropathies seems to increase the sensitivity compared to anti‐sulfatide antibodies alone (49% and 39%, respectively, with a slightly reduced specificity, from 97% to 87%), helping the characterization of otherwise undefined neuropathy that could benefit from immunomodulatory therapy.